Satisfaction with the life and quality of labor life in teachers of state educational institutions of Lima Metropolitana - Reyes Robles, Patricia (2017)
Satisfaction with Life (SCV) is the cognitive component of well-being and refers to a judgment that the individual makes of the quality of their lives according to their own unique set of criteria. In addition, its employees demand to be treated with respect, dignity and justice, a substantial part of the quality of work life (CVL). For this reason, it is necessary to know what is the relationship that exists between the SCV and the CVL that have the teachers of state educational institutions of Metropolitan Lima of the UGEL N ° 3. In the present research, an instrument has been developed to measure the quality of work life (CVL), finding that there is a relationship between SCV and CVL of teachers that is significant and slightly moderate with a negative tendency, also analyzing each of its components, as a basis for sustaining improvements in the human resources policies of the Ministry of Education in Peru.